Identification of Critical Activities and Associated Risks in Microtunnelling Construction Projects - Karisma, Aditiya Putra; Riantini, Leni Sagita; Ichsan, Mohammad (Avenew Indonesia, 2026)
Project X is forecasted to experience delays primarily due to discrepancies between tender assumptions and actual site conditions. This study aims to identify critical activities in microtunnelling construction projects and their associated risk factors. The findings are expected to provide a reference framework for effective schedule monitoring and evaluation in microtunnelling projects in Indonesia. Archival and historical data, including construction schedules and Work Breakdown Structure (WBS) documents of method statements, were collected to identify critical activities. Questionnaires and interviews were conducted with at least three experts to determine the risk factors contributing to the criticality of these activities. The results indicate that critical activities in microtunnelling projects can be categorized by work type, including permitting, preparation, shaft, pipe jacking, manhole, diversion chamber, reinstatement, administrative, and testing and commissioning works. Furthermore, various risk factors were identified across these activities, including administrative risks, external condition risks, geological risks, technical risks, country-related risks at the construction location, and safety risks related to human factors.